2007
DOI: 10.1590/s0103-50532007000400025
|View full text |Cite
|
Sign up to set email alerts
|

Multi-site PM2.5 and PM2.5-10 aerosol source apportionment in Rio de Janeiro, Brazil

Abstract: Foi realizada a amostragem de aerossol em dez locais distribuídos em diferentes regiões da cidade do Rio de Janeiro, de setembro/2003 a setembro/2004, em uma base semanal com amostragens de 24 horas. As frações do aerossol PM 2.5 e PM 2.5-10 foram amostradas usando um sistema com filtros em série. Foram determinadas: a massa do aerossol, carbono elementar, a concentração dos íons solúveis, assim como a concentração total de alumínio, cálcio, ferro, magnésio, potássio, sódio e titânio. A concentração mássica mé… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
3
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 19 publications
4
3
0
1
Order By: Relevance
“…Urca's station was the sampling point with less vehicular influence while lagoa was more impacted. The annual average Pm 2.5 concentrations observed at maracanã ranged from 6 to 13 µg m -3 , which are similar to the previous study from 2003 to 2005 (9.8 to 11 µg m -3 ) (Soluri et al 2007, Godoy et al 2009). On the other hand, previous studies performed in Recreio dos Bandeirantes registered lower concentrations of Pm 2.5 (7.7 µg m -3 ) (Soluri et al 2007, Godoy et al 2009) than in this one (11 to 16 µg m -3 ).…”
Section: Particulate Mattersupporting
confidence: 90%
See 2 more Smart Citations
“…Urca's station was the sampling point with less vehicular influence while lagoa was more impacted. The annual average Pm 2.5 concentrations observed at maracanã ranged from 6 to 13 µg m -3 , which are similar to the previous study from 2003 to 2005 (9.8 to 11 µg m -3 ) (Soluri et al 2007, Godoy et al 2009). On the other hand, previous studies performed in Recreio dos Bandeirantes registered lower concentrations of Pm 2.5 (7.7 µg m -3 ) (Soluri et al 2007, Godoy et al 2009) than in this one (11 to 16 µg m -3 ).…”
Section: Particulate Mattersupporting
confidence: 90%
“…The annual average Pm 2.5 concentrations observed at maracanã ranged from 6 to 13 µg m -3 , which are similar to the previous study from 2003 to 2005 (9.8 to 11 µg m -3 ) (Soluri et al 2007, Godoy et al 2009). On the other hand, previous studies performed in Recreio dos Bandeirantes registered lower concentrations of Pm 2.5 (7.7 µg m -3 ) (Soluri et al 2007, Godoy et al 2009) than in this one (11 to 16 µg m -3 ). Since 2008, this site has been received more influence of heavy traffic due to the construction of an expressway for bus circulation (BRT-TransOeste) and constructions of Arenas (Sport Parks) and Villages' Athletics for the Olympic Games (Ventura et al 2016(Ventura et al , 2017b, resulting in high levels of pollutants.…”
Section: Particulate Mattersupporting
confidence: 90%
See 1 more Smart Citation
“…[11][12][13] Over the last few years, several studies describing the PM 2.5 particulate matter were obtained in Rio de Janeiro City. 14,15 In 2009, Godoy et al 15 published results describing aerosol samples that were collected in ten locations in the Rio de Janeiro Metropolitan Area, and the trace elements were analyzed by inductively coupled plasmamass spectrometry (ICP-MS). After applying multivariate analysis, Godoy et al 15 concluded that soil dust is the main source of coarse aerosol particles, with sea-spray and vehicular traffic being the next most common sources.…”
Section: Introductionmentioning
confidence: 99%
“…São vários os trabalhos brasileiros relacionados à composição química do MP atmosférico em áreas influenciadas pelas emissões veiculares, industriais e atividades relacionadas à produção de energia, 6 entretanto, são poucos os estudos em áreas urbanas relacionados à composição química de substâncias inorgânicas solúveis em água associadas às PI coletadas por equipamentos que permitam seu fracionamento sob as formas de MP 2,5 e MP 2,5-10 . [7][8][9][10] No que tange à influência da queima de biomassa, associada à colheita da cana-de-açúcar e ao desmatamento de áreas do cerrado e da floresta tropical amazônica, sobre a composição química do MP atmosférico, Allen et al 11 investigaram a composição iônica (inorgânica e orgânica) em amostras de MP fino (D a < 3,5 mm) e grosso (D a > 3,5 mm ) coletadas em área rural nas proximidade de Araraquara (SP) e Yamasoe et al 12 em amostras de MP fino (D a < 2,0 mm) e grosso (D a > 2,0 mm) coletadas, no período agosto-setembro, na Reserva Ecológica do Instituto Brasileiro de Geografia e Estatística, ao sul de Brasília, e em Jamari (RO).…”
Section: Introductionunclassified